Giant Bark Aphid, Longistigma caryae (Harris) (Insecta: Hemiptera: Aphididae) - Harold A. Denmark (EDIS, 2005)
This bark-feeding aphid was first described by Harris (1841) as Aphis caryae from pignut hickory, Carya glabra (= porcina) (Mill.) Sweet, in Massachusetts. It is the largest aphid that occurs in the United States, and it was probably this species that was reported by Thomas (1879) from limbs of pignut hickory in Illinois. Weed (1891) described its various forms and gave a short note on its biology. Wilson (1909) described the genus Longistigma for this species because of the extremely long slender stigma which extends around the end of the wing. This document is EENY-292 (originally published as DPI Entomology Circular 212), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2003. Revised: May 2004.